Political economy of agricultural producer support in Malawi: An econometric test of determinants of producer protection in the maize sector - Phiri, Horace; Edriss, Abdi Khalil (International Food Policy Research Institute, 2013)
Malawi has struggled to achieve sustained agricultural growth over the last four decades. As such there is need for in-creased investment and supportive policies if greater success is to be realized. As a prerequisite to identifying the role that improved policies and investment can play, a better understanding is needed of the incentives that producers in the agricultural sector obtain currently. However, research on the subject has been scanty. For this study, annual Producer Subsidy Equivalent (PSE) for the staple food crop, maize, were calculated for the period 1970 to 2010.